Refining biomass residues for sustainable energy and bio-products: An assessment of technology, its importance, and strategic applications in circular bio-economy. (July 2020) - Awasthi, Mukesh Kumar; Sarsaiya, Surendra; Patel, Anil; Juneja, Ankita; Singh, Rajendra Prasad; Yan, Binghua; Awasthi, Sanjeev Kumar; Jain, Archana; Liu, Tao; Duan, Yumin; Pandey, Ashok; Zhang, Zengqiang; et al.
Abstract: In the circular bio-economy, effective biomass valorization through the strategic use of resources is essential in terms of generating valuable products, sustainable development, and maximizing ecological and socio-economic benefits. Technologies are being developed and improved to optimize the use of abundant biomass and to generate several value-added products. Efficient nutrient recovery requires additional energy-intensive steps for effective valorization. Moreover, appropriate waste collection and pretreatment practices increase the degree of valorization. The use of biomass waste in biorefineries has significant potential to yield biofuels and organic fertilizers. Further research and development are required to develop effective biorefining technologies to enable the efficient exploitation of bioresources. Greater consideration should be applied to energy pathways to support this technology. Therefore, there is a demand for innovation in the integrated biorefining approach in response to changing markets, and novel commercial models should be introduced into the circular economy. Highlights: Use of biomass residues in biorefineries supports as sustainable circular bio-economy. Technology assessment is a sustainable approach to assessing biomass biorefineries. Type and availability of biomass sources influence the competitiveness and social acceptability of biorefineries.